Assessment of Central Obesity Using Waist Circumference Among Patients Attending a Cardiac Hospital in Central Nepal - Laudari, Shankar; K C, Laxmi; Thapa, Anjali; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2026)
Background: Central obesity is an important cardiovascular risk factor associated with hypertension, diabetes mellitus, coronary artery disease, and metabolic syndrome. Waist circumference is a simple and reliable measure of abdominal adiposity and is widely used to assess obesity-related health risks. This study aimed to determine the prevalence of central obesity among patients attending a cardiac hospital in Central Nepal Methods: A hospital-based cross-sectional observational study was conducted among 100 patients attending a cardiac hospital in Central Nepal. Sociodemographic and clinical information were collected using a structured data collection form. Waist circumference was measured using a standardized procedure with participants in a standing position. Central obesity was defined according to the Asian-specific cutoff values of waist circumference (≥90 cm for males and ≥80 cm for females). Data were entered, cleaned, and analyzed using statistical software. Descriptive statistics, including mean, standard deviation, frequency, and percentage, were used to summarize participant characteristics and estimate the prevalence of central obesity Results: The mean age of the participants was 51.59 ± 13.61 years. Among the study population, 45% were males and 55% were females. The mean waist circumference was 92.2 ± 12.15 cm. Overall, 79 (79.0%) participants had central obesity based on the Asian cutoff criteria. Conclusion: Central obesity was highly prevalent among patients attending the cardiac hospital. Routine measurement of waist circumference may facilitate early identification of high-risk individuals and support timely preventive and therapeutic interventions to reduce cardiovascular risk.